A dictionary of marketing - Doyle, Charles, 1959- (Oxford paperback reference, 2011)
Provides over 2,600 entries on topics spanning terms for traditional marketing techniques (from strategy, positioning, segmentation, and branding, to all aspects of marketing planning, research, and analysis), as well as leading marketing theories and concepts. Covers both classic and modern marketing techniques. Reflects modern changes in marketing practice, including the use of digital media and multimedia, the impact of the world wide web on advertising, and the increased influence of social media, search engine optimization, and global marketing. Includes a time line of the development of marketing as a discipline and the key events that impacted the development. Looks at iconic brands of the 20th and 21st centuries, including advertising and brand case studies with a strong international focus.